DETERMINATION OF ARABINOSE AND GALACTOSE CONTENT IN DRY EXTRACT OF WALNUT BARK (JUGLANS REGIA) - S. S. Turayeva (Web of Journals Publishing, 2025)
The biologically active substances contained in the dry extract of walnut shells were studied. This extract was obtained from various raw materials, and the results of comparative analysis of arabinose and galactose in its content were presented.
Keywords: Juglans regia, diabetes, antioxidant, insulin, inflammation, biologically active substance, arabinose, galactose.